XMM-Newton campaign on the ultraluminous X-ray source NGC 247 ULX-1: outflows. Issue 4 (10th June 2021) - Pinto, C; Soria, R; Walton, D J; D'Aì, A; Pintore, F; Kosec, P; Alston, W N; Fuerst, F; Middleton, M J; Roberts, T P; Del Santo, M; Barret, D; et al.
ABSTRACT: Most ultraluminous X-ray sources (ULXs) are believed to be powered by super-Eddington accreting neutron stars and, perhaps, black holes. Above the Eddington rate the disc is expected to thicken and to launch powerful winds through radiation pressure. Winds have been recently discovered in several ULXs. However, it is yet unclear whether the thickening of the disc or the wind variability causes the switch between the classical soft and supersoft states observed in some ULXs. In order to understand such phenomenology and the overall super-Eddington mechanism, we undertook a large (800 ks) observing campaign with XMM-Newton to study NGC 247 ULX-1, which shifts between a supersoft and classical soft ULX state. The new observations show unambiguous evidence of a wind in the form of emission and absorption lines from highly ionized ionic species, with the latter indicating a mildly relativistic outflow (−0.17 c ) in line with the detections in other ULXs. Strong dipping activity is observed in the light curve and primarily during the brightest observations, which is typical among soft ULXs, and indicates a close relationship between the accretion rate and the appearance of the dips. The latter is likely due to a thickening of the disc scale height and the wind as shown by a progressively increasing blueshift in the spectral lines.